Impact of Tart Cherry Juice on Joint Flexibility and Pain in Individuals with Self-Reported Knee Osteoarthritis (P01-030-19). (13th June 2019) - Du, Chen; Chapman, Sarah Collins; Kwon, Young-Hoo; Vijayagopal, Parakat; Juma, Shanil
Abstract: Objectives: The purpose of this study was to examine the daily consumption of tart cherry juice in comparison to a placebo juice on symptoms associated with knee osteoarthritis in both men and woman, age 45–79 years old, for a treatment period of 120 days. Methods: In a randomized, double-blind control trial, a total of 66 adults with self-reported symptomatic knee OA, were randomized to either consume a 16 oz of tart cherry juice (TCJ) or a placebo juice daily for 4 months. Pain, mobility, plasma biomarkers of cartilage metabolism were evaluated at baseline, 2 months and 4 months. Pain, stiffness, and impact on quality of life were assessed using Self-administered Modified Short Form McGill Pain Questionnaire, while flexibility of the afflicted joint(s) was assessed via range of motion assessment (ROM). Plasma biomarkers related to cartilage metabolism such as glycoprotein 39 (YKL-40), hyaluronic acid, insulin-like growth factor(IGF)-1, and insulin-like growth factor binding protein (IGFBP-3) were determined. Results: A total of 57 participants completed the study with an attrition rate of 9%. Pain and impact on quality of life decreased significantly at mid-point in the TCJ group, but these improvements were not maintained at the final time point. At midpoint, right knee ROM increased significantly in the TCJ at mid-point, but did not maintain significant at the end of the treatment period. Knee extension and knee flexion also improved significantly in the TCJ group from baseline to midpoint, while there was no significant change in the placebo group. The TCJ group had an overall significant decrease in plasma YKL-40, a marker of cartilage destruction, while no changes were observed in the placebo group. A significant decrease in the plasma IGF-1 and a non-significant up trend in IGFBP-3 were observed in the placebo group, while in the TCJ group no changes in IGF-1 and a non-significant decrease in IGFBP-3 was observed. There were no changes in the hyaluronic acid in the TCJ group during the study duration, but a non-significant up trending was noticed in the placebo group. Conclusions: The findings of the study suggest that daily consumption of tart cherry juice results in improvement in mobility, relief of pain-related symptoms and quality of life, and selective markers of cartilage health. Funding Sources: Cherry Marketing Institute.